Complex genetic signatures in immune cells underlie autoimmunity and inform therapy - Orrù, Valeria; Steri, Maristella; Sidore, Carlo; Marongiu, Michele; Serra, Valentina; Olla, Stefania; Sole, Gabriella; Lai, Sandra; Dei, Mariano; Mulas, Antonella; Virdis, Francesca; Piras, Maria Grazia; et al. (Nature genetics, 2020)
We report on the influence of ~22 million variants on 731 immune cell traits in a cohort of 3,757 Sardinians. We detected 122 significant ( P < 1.28 × 10 −11 ) independent association signals for 459 cell traits at 70 loci (53 of them novel) identifying several molecules and mechanisms involved in cell regulation. Furthermore, 53 signals at 36 loci overlapped with previously reported disease-associated signals, predominantly for autoimmune disorders, highlighting intermediate phenotypes in pathogenesis. Collectively, our findings illustrate complex genetic regulation of immune cells with highly selective effects on autoimmune disease risk at the cell-subtype level. These results identify drug-targetable pathways informing the design of more specific treatments for autoimmune diseases. An analysis of 3,757 Sardinian genomes identifies 122 association signals for 459 immune cell traits at 69 loci. Some variants are associated with autoimmune disorders.